PENERAPAN METODE PEMBELAJARAN AKTIF DALAM MATERI PENDIDIKAN AGAMA ISLAM UNTUK MENUMBUHKAN KARAKTER KEMANDIRIAN SISWA DI SMK MUHAMMADIYAH 2 BOJA - Okta Khairul Hikmah; Syaiful Hadi (As-Sulthan Journal of Education, 2025)
This study aims to analyze how active learning methods are applied in Islamic Religious Education (PAI) subjects to foster students' independent character at SMK Muhammadiyah 2 Boja. We used a qualitative approach with a case study design for this study. We collected data through observation, interviews, and documentation. From the results of the study, it can be seen that the application of active learning methods such as problem-based learning, cooperative learning, and project-based learning can increase students' independence, both in learning and in everyday life. This method makes students more active in finding learning resources, more confident in expressing opinions, and able to develop problem-solving skills independently. In addition, active learning also helps students to be more responsible for their assignments and improves their ability to manage time and plan learning. The factors that support the implementation of active learning methods include teacher commitment to implementing innovative learning strategies, support from a supportive school environment, and students' awareness of the importance of independent learning. However, this study also found several obstacles, such as students' lack of readiness to adopt more independent learning methods, limited facilities and infrastructure, and limited time to implement active methods in class.